Sekolah Yang Berorientasi Budaya Mutu - Haris Alfuadi (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Organizational culture is a pattern of beliefs and values ​​(values) of the organization that are understood, imbued and practiced by the organization so that the pattern gives its own meaning and becomes the basis for rules of behavior (individuals and groups / units) in the organization. In the context of schools, the culture of quality-based school organizations is very much determined by leadership and managerial behavior in anticipating various problems and obstacles that arise as a result of external adaptation and internal integration that are running quite well in directing organizational behavior to focus on quality. Quality culture in schools can be manifested in the fields of curriculum / teaching, staffing, student affairs, finance, facilities and infrastructure, relations with the community with standard management standards in its achievement to provide customer satisfaction, and the best service so as to produce superior graduate products and best services towards school stakeholders.